ANALISIS EKSPRESI PENOLAKAN DALAM FILM REMAJA BERJUDUL â€œTHE CLIQUEâ€: SEBUAH PERSPEKTIF PRAGMATIK - Arini Hidayah; Dyah Subekti (Universitas Musamus Merauke, 2022)
The purposes of this research are to analyze the types of refusal expressions employed by the characters, to determine the strategies that used in each type of refusal expressions and to know how the refusal expressions is expressed in the movie entitled â€œThe Cliqueâ€. This research is basically a conversation analysis. This research is a qualitative research. The sources of data in this research were selected script dialogs of the conversations in the movie. The conclusions are: (1) There are 20 dialogues containing refusal found in the movie entitled â€œThe Cliqueâ€ in which 12 dialogues are direct refusal and 8 dialogues are indirect refusal; (2) There are six strategies that used; (3) The characters in the movie express directly and indirectly. The characters perform the refusal directly because they want to convey the meaning of what they say explicitly. On the other hand, the characters choose to perform the refusal indirectly because they want to maintain a harmonious relationship with whom they talk, make oneâ€™s language more/less interesting, increasing the force of oneâ€™s message, and competing goals.